The Contribution of Ss. Cyril and Methodius to Culture and Religion - Hetényi, Martin (Religions, 2021)
The Byzantine mission of saint brothers Cyril and Methodius had a major impact on the spiritual history of Great Moravia. In the centuries that followed, their works paved the way for the political and historical development of the Slavic nations, mainly in South-East and East Europe. The mission, which reached Great Moravia in 863, had several dimensions. The most important were evangelism and the cultural and civilizational dimensions. Translations of the Gospel and liturgical texts into Old Church Slavonic intensified the religious life of our ancestors and laid the foundations of literature and culture for almost the entire Slavic world. From this point of view, research should be focused on the role and reflection of this historical and cultural heritage in the ecclesiastical and spiritual, national and cultural life of the Slavic nations. The aim of this article is to assess the significance of Christian and Byzantine cultural values in terms of the collective Slavic identity. The Cyrillo-Methodian idea manifests itself in the history of the Slavic world as a complex but solid foundation, capable of renewing the sleeping or inhibited energy and values in the areas of faith, culture, literature, arts, education, upbringing, as well as national consciousness.